Reflection of Preparing and Implementing Budgets According to Modern Methods on Government Performance - Aqeel Gatea Jabbar; Rawad Kareem Salloomi (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
The study aimed to find out the nature of the budget, know the modern techniques of preparing and implementing the budget, and the consequences of preparing budget based on the modern techniques on performance of government. The descriptive-analytical approach was used to meet the objectives and hypotheses of the research. The data was gathered through a questionnaire whereby 60 questionnaires where distributed to a sample population of accountants working in the Financial Affairs Department at the General Directorate of Education in Wasit Governorate (Iraq), and 57 questionnaires were collected to establish the views of the accountants regarding the effect of preparing and implementing budgets under the modern techniques on the government performance. This paper came up with a number of conclusions. Preparation of the general budget of the state is a technical and political process that involves and is involving different actors in the state. The budget preparation process is a technical process since it involves numerous key calculations that can be used to quantify the anticipated revenues, the cost of activities likely to be obtained in the year and estimation of the planned expenditures. The process of preparing the budget through the traditional ways (line-item budgeting) does not contribute to the optimal planning and budget allocation of the state and, therefore, the fulfillment of the goals laid out by the countries. This paper advises on the need to focus on the current approaches in the budget preparation because they enhance governmental performance, enhance the effectiveness and efficiency of state expenditures, strive to diversify the income, and convert the policies and goals of the state into a definite and actualized reality on the ground, with the help of standards and indicators that modern means of preparing the budget have offered. And to act to modernize the budget system in Iraq, profiteering with the experience of other countries in this domain, and that modernization be a progress, commencing with the budgeting of some ministries or departments within ministries and bodies gradually with the aim of acquiring more experience and expertise, and then meet the impediments which will emerge to proceed to a complete transition.